Memes of Misinformation : Unraveling the controversial, socio-economic and political issues behind those annoying social media memes. - Castañeda Jr., Julio C. (Vernon series in communication., 2017)
In this first installment of the Misinformation series, the author tackles complex socio-economic and political topics related to the economy of the United States, such as the federal budget, wasteful spending, the national debt, unemployment and social security. By breaking down each subject into layman's terms, the author clearly and concisely presents, in an unbiased manner, the facts behind the fake news, half-truths and general misinformation from the annoying headlines and memes cluttering social media on these volatile subjects.